2020
DOI: 10.1177/0269215519897414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kinesiotaping and exercise program on patients with obesity-induced coccydynia: a randomized, double-blinded, sham-controlled clinical trial

Abstract: Objective: To investigate the effect of kinesiotaping and a designed exercise program versus sham kinesiotaping and the same exercise program on pain, range of motion, and activities of daily living in obese patients suffering from coccydynia. Design: A double-blinded, randomized, sham-controlled trial. Setting: Outpatient, Cairo University hospitals. Participants: Sixty patients with coccydynia randomized equally into kinesiotape plus exercise and sham kinesiotape plus exercise groups. Intervention: The kines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Sixty three studies were included for data extraction. 1,9-13,15-21,23,27-75 No articles were included through the search in relevant journals, nor through reference and citation screening (see flowchart of literature screening, Figure 1).
Figure 1.Prisma Flowchart.
…”
Section: Resultsmentioning
confidence: 99%
“…Sixty three studies were included for data extraction. 1,9-13,15-21,23,27-75 No articles were included through the search in relevant journals, nor through reference and citation screening (see flowchart of literature screening, Figure 1).
Figure 1.Prisma Flowchart.
…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of KT for pain relief and functional disability enhancement has been reported in several studies 19,33,34 . KT has been proposed as an efficient method for enhancing blood and lymphatic circulation, realigning joints, and normalizing muscle tension [21][22][23] .…”
Section: Discussionmentioning
confidence: 96%
“…Current literature provides several options for the conservative management of Coccydynia; non-steroidal anti-inflammatory drugs, ring-shaped cushions, Levator ani relaxation exercises, and gentle massage over the ligaments attached to the sacrococcygeal joint 8 , 13 . Physical therapy modalities include interferential current 14 , shortwave diathermy 15 , extracorporeal shock wave therapy 16 , stretching of the Piriformis and Iliopsoas muscles 17 , coccyx manipulation 18 , and kinesiotaping (KT) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[37,39] However, when conservative management and injections are ineffective, a surgical procedure is recommended, and a coccygectomy is carried out, which has resulted in good outcomes. [3,34,37,40] However, this surgical treatment is associated with challenges such as a high probability of infection and complex follow-up care. [21] As per research, coccygectomy has a complication rate ranging from 0 to 50%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients describe the pain as sharp, stabbing or aching pain in the coccygeal segments [8,33] Pain can be mild but severe cases are reported with agonizing pain that affects the daily functioning of individuals. [34] Previous studies have shown that pain is experienced particularly when sitting on hard surfaces. [1] Activities that cause strain on the levator ani muscle are found to be associated with aggravation of symptoms.…”
Section: Introductionmentioning
confidence: 99%